Biosorption of cadmium using moss (hyophila involuta). - Ruefa, Maila J. 4 0 16; 5 (2005)
ABSTRACT: This study is primarily concerned with the Biosorption capacity of Mosses (Hyophila involuta).The study includes the effect of Cadmium on the chloroplast count growth rate and sorption rate the of moss. Mosses were collected from the walls of Intramuros, Manila on November 30, 2004 at 10:00 a.m. and the following morning were exposed to different concentrations of Cadmium (Cd) 10 ppm, 20 ppm and 40 ppm, control set up using tap water was also prepared. The experiment lasted for 12 days. Every other day chloroplast number, growth rate and sorption rate were measured. After 12 days of experimentation, statistics results using one-way ANOVA and Turkey analysis showed that exposure of moss to cadmium had no significant difference compared to the control set up when it comes to growth measured by biomass and chloroplast counted by tissue slide preparation. Also, the rate of absorption of moss was measured using AAS at de la Salle University and it likewise showed no significant difference.
Thesis :(B.S. Biology) Pamantasan ng Lungsod ng Maynila, 2005.
Keywords: 2 -- 0; 6; 20; 20; 2